PKM Inisiasi Industri Mikro Pengolahan Plastik Limbah Kemasan Makanan dan Minuman - Desa Wringinsongo, Kec-Tumpang, Malang - Pudji Herijanto; Nilawati Fiernaningsih; Widjanarko Widjanarko; Ahmad Fauzi; Maskur Maskur; Mahmudatul Himmah (Jurnal Pengabdian kepada Masyarakat, 2023)
Mitra Pengabdian Masyarakat is a waste bank that manages various waste generated by households. One of the dominant types of waste is plastic waste of beverage and food packaging, which are types 1 and 5. This waste has high economic value if processed into displays, as raw material for recycled products. Around the village there are a number of sources of plastic waste. Thus, this waste bank has the potential to become a micro industry for displaying plastic waste, food and beverage packaging. The purpose of this PkM is to initiate waste banks into plastic production units for the plastic recycling industry.The method carried out is to improve the ability of waste tire managers to become production system managers. For this reason, training on production system management was given to waste bank managers. Then training on the operation and maintenance of plastic chopper machines is given. After that, assistance is carried out so that they can run the production system. As a result, they already understand the management of the plastic display production system for food and beverage packaging waste. In addition, it can also produce products according to consumer needs. This production unit can only run next year, because it requires an injection of capital to be obtained from the 2024 village budget allocation.